INCREASING CHILDREN'S INTEREST IN READING THROUGH A READING GARDEN IN THE PLAY AREA OF THE PANGGUNGREJO VILLAGE, PASURUAN CITY - Eni Erwantiningsih; Putri Marina Dewi; Muhammad Tajuddin; Eka Farhan Iskandar; Firdhaus Putra Perdana (International Journal of Engagement and Empowerment, 2023)
Reading is a window to see the world with all its progress and development. Reading is also able to change one's way of thinking and perspective on something. Panggungrejo sub-district is a coastal area in the city of Pasuruan with the majority of the population only having education up to junior high school. According to the people's view, if someone is able to catch fish in the sea, then he is ready to get married. So to get a higher education is no longer necessary. Through the activities of the real work lecture program, Merdeka Pasuruan University students try to provide a forum for the community for reading activities namely a reading garden. Students take advantage of the semi-permanent building where the children and their mothers wait for their fathers who are fishing. With this literacy improvement activity it is hoped that both children and housewives will be able to increase their interest in reading and broaden their knowledge in their spare time. With the opening of the horizons of thinking, the desire to get a higher education is expected to be the main choice of the community to improve the quality of life